Effect of OATP1B1/1B3 Inhibitor GDC-0810 on the Pharmacokinetics of Pravastatin and Coproporphyrin I/III in Healthy Female Subjects - Liu, Lichuan; Cheeti, Sravanthi; Yoshida, Kenta; Choo, Edna; Chen, Eugene; Chen, Buyun; Gates, Mary; Singel, Stina; Morley, Roland; Ware, Joseph; Sahasranaman, Srikumar (Journal of clinical pharmacology, 2018)
Developed as an oral anticancer drug to treat estrogen receptor-positive breast cancer, GDC-0810 was shown to be a potent inhibitor of organic anion-transporting polypeptide 1B1 and 1B3 (OATP1B1/1B3) from an in vitro assay. A clinical study was conducted to assess the drug-drug interaction potential between GDC-0810 and pravastatin, which is a relatively selective and sensitive OATP1B1/1B3 substrate. Fifteen healthy female subjects of non-childbearing potential were enrolled in the study. On day 1 in period 1, a single 10-mg dose of pravastatin was administered to all subjects. Following a 4-day washout period, 600 mg of GDC-0810 was administered once daily on days 5 through 8 in period 2 to achieve steady-state concentrations. On day 7, a single dose of 10-mg pravastatin was coadministered with the 600-mg GDC-0810 dose. Concentrations of pravastatin (periods 1 and 2) and GDC-0810 (period 2 only) were quantified in blood samples and subsequently used to calculate the pharmacokinetics (PK) parameters. The pravastatin mean maximal concentration and area under the curve values were approximately 20% and 41% higher, respectively, following pravastatin coadministration with GDC-0810 compared to pravastatin alone. Based on the magnitude of change in this drug-drug interaction study, dose adjustments for pravastatin (and other OATP1B1/1B3 substrates) were not considered necessary when administered with GDC-0810. Retrospectively, the endogenous biomarkers of OATP1B1/1B3, coproporphyrin I and III, were also measured and showed changes comparable to those of pravastatin, indicating their utility in detecting weak inhibition of OATP1B1/1B3 in the clinical setting.